The Effect of Distance Instruction Based on the ARCS Motivation Model on the Course Interest - Alanoglu, Muslim; Karabatak, Songul; Karabatak, Murat (Institute of Electrical and Electronics Engineers Inc., 2023)
This study examined the effect of distance instruction based on the ARCS motivation model supported by instructional videos on learners' course interest levels. The effectiveness of the instruction model used was also examined in the study. The participants of the experimental study consisted of 194 teacher candidates studying at Firat University in the spring term of 2021-2022. To collect the research data, the Course Interest Scale and Instruction Scale Based on the ARCS Motivation Model were used. In the study, it was concluded that while the confidence dimension of the instruction was carried out most effectively, the satisfaction dimension was performed the least effectively. In addition, the instruction based on the ARCS motivation model increased the teacher candidates' course interest levels. © 2023 IEEE.
11th International Symposium on Digital Forensics and Security, ISDFS 2023 -- 11 May 2023 through 12 May 2023 -- TN -- 189042
Keywords: ARCS motivation model; course interest; distance education; instruction